Tinjauan Yuridis Terhadap Proses Perencanaan Dan Pembangunan Daerah Dalam Penyelenggaraan Pemerintahan Dan Pembangunan Daerah Provinsi Sumatera Utara (Studi Pada Bappeda Provinsi Sumatera Utara) - Ervina Sari Sipahutar (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2018)
AbstractDevelopment by Bappeda (Development Planning Agency at Sub-National Level) always places, maintains and develops the development plans in the regions so that the results of this study can be used as an effort to implement the planning system and the regional development process.  It is hoped that safe, smooth, orderly, healthy and efficient life and livelihoods can be realized in the well planned spatial utilization.               Planning and development processes are arranged systematically and sequentially using qualitative and educative data. The collected data will be analyzed using a thinking method starting from the general thing. Any assumptions about reality or social phenomena will be drawn to new information to be used as achievement, building in planning a directed and integrated development process.               When planning always goes increasing, a development planning in each region is needed through regional planning. The planning are oriented towards the future and seek to build a community with long-term and large-scale planning.               In accordance with Law No. 2 of 2004 concerning the National Development Planning System, which also refers to Government Regulation No. 41 of 2007 concerning Regional Device Organizations.               Regional development planning is basically a plan that shapes the community system against the faced conditions to realize development in the region.               In practice, the implementation of development in the regions is based on the planning and development process in the      above areas involving agencies in the province by the Provincial Bappeda. To accommodate the community's desire for development, a bottom-up planning system is adopted. This is actually participatory planning. The lowest stage in the regional development coordination meeting will be followed at a higher level.               The realization of the Bappeda of North Sumatra Province is to develop a regional development plan both long-term, medium-term, short-term, poverty alleviation, and to coordinate all development plans with vertical agencies and agencies in the North Sumatra province. Keyword: Regional Development Planning, Organizing governance and development, the Role of the Regional Development Planning Agency